Senior Citizens Protesting at Exhibit Hall Mayor Dan Whitehurst Funding Policies - Watkins, Howard::::::::: (1981)
Marque "11/23 WHITEHURST FOR SENATE DINNER 6 PM" above Whitehurst sign held up by Kathy Reilley